Influences of Programs and Organizations on the Adoption of Sustainable Land Management Technologies in Uganda - Jagger, Pamela; Pender, John L. (International Food Policy Research Institute, 2006)
Governments are devolving service and infrastructure provision, regulatory authority, and decisionmaking in many developing countries. Market reforms and structural adjustment policies devolve the provision of services and infrastructure to nongovernmental organizations (NGOs), community-based organizations (CBOs), and the private sector (Farrington and Bebbington 1993; Uphoff 1993; Pender and Scherr 2002). The transition from the provision of extension services, input supply, rural credit delivery, regulation, and other aspects of natural resource management from centralized governments to alternative institutions may have significant implications for the capacity of smallholders to sustainably manage their resources.